Menumbuhkan Kreativitas Siswa MI/SD Melalui Kegiatan Eksperimen Fisika “Balon Ditusuk Tanpa Melutus Dalam Pembelajaran IPA di MI Malik Ibrahim Jenggawah - Tri Hany Nur Safitri; Muhammad Suwignyo Prayogo; Nabila Sevidiana (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2025)
This study aims to foster creativity in elementary school students through a simple physics experiment activity called "A Balloon Pierced Without Popping." This activity is designed to provide a fun learning experience and encourage students to think scientifically through the process of trying and discovering basic physics concepts themselves. The study used a qualitative approach with descriptive methods. The subjects were 25 third-grade students at one of the Islamic Elementary Schools (MI) Malik Ibrahim Jenggawah, who participated in the experiment activity for one meeting. Data were collected through observation, interviews, and documentation, then analyzed descriptively qualitatively. The results showed that the simple physics experiment activity was able to improve students' creativity, as seen from their courage in expressing ideas, making predictions, and finding solutions to problems that arose during the experiment. In addition, students showed a high level of curiosity and enthusiasm in participating in the learning process. Thus, the "Balloon Pierced Without Popping" experiment activity is effective in fostering creativity and interest in learning science in elementary school students.